DIFFERENT OPINION ON THE AMOUNT OF AL-QUR’AN VERSES AND ITS IMPLICATION TO THE PUBLISHING MUSHAF AL-QUR’AN IN INDONESIA - Moh. Zahid (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2017)
Imam Qurra have different opinions in calculating the amount of verses in Qur’an, they are: 1) Al-Madanî al-Awwal stated that there are 6217 or 6214 verses, 2) Al-Madanî al-Akhîr mentioned that there are 6214 verses, 3) Ahl Mekkah stated that there are 6210 verses, 4) Ahl Bashrah counted for 6204 verses, 5) Ahl Damaskus stated that there are 6227 or 6226 verses, 6) al-Humushi stated that there are 6232 verses, and 7) ahl Kufah mentioned that there are 6236 verses. While the Mushaf al-Qur’an published in Indonesia have 6236 verses. Therefore, The Indonesian Standard Mushaf followed the opinion of Kûfiy, They are Imam 'Asim (127/744), Imam Hamzah (156/772), Imam Al-Kisa'i (189/804) Khalaf al-Asyir (229/843) and al-A’masy (148/765).